To determination of locking effort of clamping devices of shoe tree type - Довбня, Н.П.; Бондаренко, Л. М.; Бобырь, Д.В. (Problems of Tribology, 2014)
Effort is found for stopping up of cylindrical details taking into account their inclination and moment. It is well-proven that effort of stopping up depends on the corner of circumference the shoe tree of detail and at coal of circumference equal 100° effort differs to 15% from a size, got without his account.